PENGUASAAN HARTA WARISAN SECARA MELAWAN HUKUM MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA - Heru Guntoro (Nusantara Hasana Berdikari, 2022)
The research case in the Decision of the Supreme Court of the Republic of Indonesia Number 889 K/Pdt/2018 in which the Business and Management of the Women's Clothing Trade Business